Nitrogen cycling in a high-nutrient tidal river revealed through high-resolution sampling and nitrate isotope mixing models - Josh Guyat; Douglas R. Tait; James Z. Sippo; Benjamin T. Stewart; Angus Ferguson; James A. Padilla-Montalvo; Christopher Ralph; Jenny Rogers; Merran Griffith; Dirk V. Erler; Michael Ingram; Damien T. Maher (Geochimica et Cosmochimica Acta, 2026)

Overlooked seasonal groundwater nutrient fluxes rival anthropogenic point sources across a variable land‐use tidal river - James A. Padilla‐Montalvo; Douglas R. Tait; Michael J. Reading; Benjamin T. Stewart; Angus Ferguson; Iremar Fernandez‐Vazquez; James Z. Sippo; Shivanesh Rao; Mitch Call; Christopher Ralph; Josh Guyat; Jenny Rogers; et al. (Limnology and Oceanography, 2025)
Understanding groundwater–surface water connectivity in tidal freshwater zones is essential for managing ecosystems within the riverine–estuarine continuum. Groundwater discharge is a key source of dissolved nutrient loads that can lead to eutrophication, deoxygenation, and other ecosystem imbalances in coastal environments. However, groundwater is an often‐overlooked nutrient delivery pathway, with limited studies quantifying groundwater inputs into freshwater transitional zones. Here, we quantify groundwater discharge and its associated nutrient fluxes along a ≈ 75 km section of a tidal freshwater zone within the Hawkesbury–Nepean River (New South Wales, Australia), which is surrounded by multiple land uses. High‐resolution timeseries and spatial surveys were employed over three hydrologically distinct seasons using the naturally occurring radioisotope tracer, radon. Survey results revealed decreasing surface water radon activity and nutrients toward the downstream estuarine boundary. Estimated groundwater discharge rates were highest in the upstream reaches (6.0–12.5 cm d −1 ), regardless of seasonal hydrological dynamics, and decreased downstream, aligning with a reduction in irrigation‐dependent agricultural practices and a change in adjacent catchment morphology. During the dry period, groundwater accounted for up to ≈ 68% of upstream river inputs. Groundwater discharge was also a major source of dissolved inorganic nitrogen, contributing between 0.8 and 1.1 times the inputs from local wastewater treatment plants, and up to 15 times more phosphate than upstream river sources. These findings highlight the role of groundwater discharge as a nutrient driver for tidal freshwater zones, which could have significant implications for future management strategies in these environments.

Restoring the seagrass Zostera muelleri with transplants: small cores are as effective as larger plots - Fleur E. Matheson; Graeme Mackay; Crispin Middleton; Richard Griffiths; Ricky Eyre; Josh Smith; Ron Ovenden (New Zealand Journal of Marine and Freshwater Research, 2023)
Seagrass extent has declined globally, including in New Zealand. Following the success of an initial trial to transplant and re‐establish intertidal seagrass at a former site in Whangarei Harbour, a second trial was initiated. This trial aimed to restore seagrass at a more distant former site and tested the efficacy of transplant units ranging in size from small cores (5 or 9 × 0.01 m diameter cores placed within a 0.25 m 2 plot) to larger entire plots (0.25 m 2 or 0.5 m 2 ). Seagrass was transplanted in winter when plants were dormant. Plant cover of transplanted and donor plots and light climate at both sites were monitored over a period of four years. All but one of the 24 units survived, and the plants began to spread after 12–18 months to eventually develop patches ranging in size from 5 to 68 m 2 . Seagrass recolonised all donor plots completely within 10 months. Results show that small cores and larger plots can both be used successfully to transplant and restore populations of Zostera muelleri with no long‐lasting damage to donor meadows. However, use of small cores is recommended to minimise extractions and loss of transplanted material, and to simplify logistics.

The power of eDNA sampling to investigate the impact of Australian mega-fires on platypus occupancy - Emily F. McColl-Gausden; Josh Griffiths; Luke Collins; Andrew R. Weeks; Reid Tingley (Biological Conservation, 2023)

Understanding and managing the interactive impacts of growth in urban land use and climate change on freshwater biota: A case study using the platypus ( Ornithorhynchus anatinus ) - Rhys A. Coleman; Yung En Chee; Nick R. Bond; Andrew Weeks; Josh Griffiths; Melody Serena; Geoff A. Williams; Christopher J. Walsh (Global Change Biology, 2022)
Globally, urban expansion and climate change interact to threaten stream ecosystems and are accelerating the loss of aquatic biodiversity. Waterway managers urgently need tools to understand the potential combined impacts of urbanization and climate change and to identify effective mitigating management interventions for protecting freshwater biota. We address this challenge using the semi‐aquatic mammal the platypus ( Ornithorhynchus anatinus ) as a focal species. We developed high‐resolution environmental spatial data for stream networks and spatially explicit habitat suitability models (HSMs) to explore the impact of threats and to identify the combination of management actions most likely to maintain or improve habitat suitability over the next 50 years in greater Melbourne, Australia. We developed and evaluated platypus HSMs (males‐and‐females and females‐only) including validation using an independent environmental DNA data set. Platypus occurred more commonly in larger, cooler streams with greater catchment‐weighted discharge, following periods of greater stream flow. They were positively associated with near‐stream forest cover and negatively associated with annual air temperature and urban stormwater runoff. Extensive reductions in suitable platypus habitat are predicted to occur under urbanization and climate change scenarios, with the greatest threat expected from reduced streamflows. This emphasizes the importance of maintaining flow regimes as part of conserving platypus in the region; however, substantial additional benefit is predicted by concurrent riparian revegetation and urban stormwater management efforts (that also have the potential to contribute to the streamflow objectives). Provision of adequate streamflows in a future with increasing water demands and water security requirements will likely require creative integrated water management solutions. Our high‐resolution stream network and HSMs have allowed predictions of potential range‐shifts due to urban expansion and climate change impacts at management‐relevant scales and at the whole‐of‐landscape scale. This has enabled systematic strategic planning, priority action planning and target setting in strategic policy development.

High levels of genetic divergence between Tasmanian and Victorian platypuses, Ornithorhynchus anatinus, as revealed by microsatellite loci - Elise Furlan; Paul A. Umina; Paul J. Mitrovski; Nick Gust; Josh Griffiths; Andrew R. Weeks (Conservation Genetics, 2010)